High Hepatic SCD1 Activity Is Associated with Low Liver Fat Content in Healthy Subjects under a Lipogenic Diet - Silbernagel, Günther; Kovarova, Marketa; Cegan, Alexander; Machann, Jürgen; Schick, Fritz; Lehmann, Rainer; Häring, Hans-Ulrich; Stefan, Norbert; Schleicher, Erwin; Fritsche, Andreas; Peter, Andreas (The journal of clinical endocrinology and metabolism, 2012)
Context:Increased hepatic de novo lipogenesis (DNL) in response to dietary sugar is implicated in the pathophysiology of fatty liver. Saturated fatty acids are the product of DNL and exert lipotoxic effects that promote liver fat accumulation. Desaturation of fatty acids by stearoyl-CoA desaturase 1 (SCD1) can prevent these deleterious effects. Here we investigated whether DNL and SCD1 are activated in parallel by dietary sugar and influence liver fat accumulation.Methods:In 20 healthy subjects (eight females and 12 males, aged 30.5 ± 2.0 yr, body mass index 25.9 ± 0.5 kg/m2) who received a 4-wk lipogenic diet supplemented with 150 g/d of monosaccharides, hepatic SCD1 activity and DNL were determined using validated fatty acid ratios (16:1n-7/16:0; 16:0/18:2n-6) in very low-density lipoprotein triglycerides. Liver fat content was measured by localized 1H-magnetic resonance spectroscopy.Results:At baseline, liver fat content was positively associated with the DNL (r = 0.54, P = 0.01) but not the SCD1 activity index (r = 0.16, P = 0.49). Dietary sugar supplementation increased liver fat content and DNL and SCD1 activity indices (+33, +19, and +8%, respectively). The increase of the DNL index was strongly related to the changes in liver fat content during the sugar supplementation (r = 0.75, P = 0.0001) but showed no association with changes in the SCD1 activity (P > 0.35). After the monosaccharide supplementation, the DNL index was still positively associated with liver fat content (r = 0.52, P = 0.02), whereas SCD1 activity showed a strong negative correlation with liver fat content (r = −0.63, P = 0.002).Conclusions:DNL is closely linked with hepatic steatosis under dietary conditions rich in monosaccharides. Our data suggest that the individual hepatic SCD1 activity is a determinant of liver fat accumulation under lipogenic dietary conditions.